PENGEMBANGAN E-LKPD DENGAN TEMA PELESTARIAN HUTAN MANGROVE TEKS BERITA KELAS VII SMP - Fitria, Maulina; Puspitasari, Mega (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The development of E-LKPD for news text in class VII junior high school is an implementation of integrating technology with learning that can be utilized in meaningful and flexible learning activities, especially assessment. This research uses the Research and Development (R&D) method using the 4D research model. This research used several data collection techniques, including: interviews, observations, and questionnaires. The test subjects of this study were students of class VII-B at SMPN 7 Bangkalan, totaling 5 people in the small group test and totaling 26 people in the large group test, as well as five expert validators of E-LKPD feasibility. The output of this E-LKPD development is in the form of an application that has been validated by five validators. The percentage obtained from: (1) content feasibility validation is 96.66%; (2) language feasibility validation is 95%; (3) presentation feasibility validation is 82.85%; (4) graphic feasibility validation is 93.33%; and (5) construct feasibility validation is 88.57%. Then, the results of the learner response questionnaire test obtained a score of 87.65% in the small group test and 83.27% in the large group test with a very feasible caterogy to be used in learning.